Effect of gender and stroke rate on joint power characteristics of the upper extremity during simulated rowing - Attenborough, A. S.; Smith, R. M.; Sinclair, P. J. (Journal of Sports Sciences, 2012)
Males typically have greater upper body strength than do females, which is likely to impact on the rowing techniques adopted by each sex. The aim of this study was to quantify energy contributions and compare the joint power production of upper extremity joints between the sexes. Seven males and eight females performed 60 s trials at five different stroke rates. External forces were measured at the handle and stretcher, while kinematics were recorded by motion analysis. Joint moments were derived by inverse dynamic calculations, followed by the calculation of joint powers and gross mechanical energy expenditure. Male rowers expended more total external energy per stroke and made a larger percentage contribution of angular shoulder energy to their total external energy expenditure. As stroke rate increased, the contribution from elbow and angular shoulder energy contributions decreased for both males and females. Female rowers decreased their angular shoulder contribution at a slower rate than did males as stroke rate increased. The overall percentage of work done on the stretcher was higher for male rowers, and this difference further increased at higher stroke rates. The results of this study suggest that specific upper body conditioning may be particularly important for female rowers.